STRATEGI MEWUJUDKAN JIWA KEWIRAUSAHAAN PADA SANTRI MELALUI EKONOMI KREATIF DALAM MENGHADAPI TANTANGAN EKONOMI GLOBAL (STUDI KASUS DI PONDOK PESANTREN DDI MANGKOSO) - Suarni, Agusdiwana; Haanurat, A. Ifayani; Arni, Arni (Jurnal Ar-Ribh, 2021)
This study aims to determine the strategy of realizing an entrepreneurial spirit in santri through the creative economy in facing the challenges of the global economy (a case study at the DDI Mangkoso Islamic boarding school). The type of research used in this research is field research which produces descriptive data in the form of written or oral data of people (informants) and observed behavior. While the data research techniques used in this study were interviews, observation, and documentation. The number of respondents was 12 respondents consisting of 10 students, 1 school principal, 1 boarding school supervisor. The results of this study indicate that in fostering the entrepreneurial spirit of the santri at the DDI Mangkoso Islamic boarding school, the boarding school cooperative and several alumni organized training on entrepreneurship to students through practices such as managing something from used materials so that it has a selling value. As for the implementation of the creative economy that can be developed at the DDI Mangkoso Islamic boarding school, such as: handicrafts and arts products, short films, design and advertising.